History of ethics essential readings with commentary - Crisp, Roger 1961-; Star, Daniel 1971- (Blackwell readings in the history of philosophy, 2020)
As the most recent addition to the Blackwell Readings in Philosophy series, History of Ethics: Essential Readings with Commentary brings together rich and varied excerpts of canonical work and contemporary scholarship to span the history of Western moral philosophy in one volume. Editors Star and Crisp, noted scholars in their fields, expertly introduce the readings to illuminate the main philosophical ideas and arguments in each selection, and connect them to broader themes. These detailed and incisive editorial commentaries make the primary source texts accessible to students while guiding them chronologically through the history of Western ethics.Structured around a thematic table of contents divided into three distinct sections, History of Ethics charts patterns in the development of ethical thought across time to highlight connections between intellectual movements. Selections range from the work of well-known figures such as Plato, Aristotle, Nietzsche, and Mill to the work of philosophers often overlooked by such anthologies, including Butler, Smith, Sidgwick, Anscombe, Foot, and Frankena. Star and Crisp skillfully arrange the collection to connect readings to contemporary issues and interests by featuring examples such as Aquinas on self-defense and the doctrine of double effect, Kant on virtue, and Mill's The Subjection of Women.